Kontribusi Lembaga Filantropi Islam Berbasis ZIS untuk Meningkatkan Kesejahteraan Masyarakat di Desa Adipura Kencana Kecamatan Sungai Bahar Kabupaten Muaro Jambi - Sintia Eka Putri; H. Sissah (Jurnal Penelitian Ilmu Ekonomi dan Keuangan Syariah, 2024)
This research explores the contribution of ZIS-based Islamic philanthropic institutions in improving community welfare in Adipura Kencana Village, Sungai Bahar Sub-district, Muaro Jambi District. The aim of this study is to understand the contributions, impacts, and efforts of ZIS-based Islamic philanthropic institutions in supporting business capital assistance programs in Sungai Bahar Sub-district, Muaro Jambi District. This research employs a descriptive qualitative method, using both primary and secondary data. Data collection techniques include observation, interviews, and documentation, while data analysis is conducted using domain, taxonomic, and componential analyses. The results indicate that direct fund distribution by the institution significantly strengthens the relationship and sense of kinship between the community and the philanthropic institution. Through direct interaction with the community, prospective aid recipients are more open in expressing their concerns and needs, making the assistance provided by the philanthropic institution highly beneficial. The community feels a considerable positive impact from the presence of Islamic philanthropic institutions managing zakat in their area, as many individuals are able to improve their welfare through productive enterprises thanks to the assistance provided by the institution. The institution carefully selects aid recipients to ensure that assistance reaches those who truly need it. However, some community members still feel they belong in the less-privileged category yet have not received assistance from the institution.